Formulation of Microemulsion-based Gel Containing Mango Seed Kernel Extract for Application in Anti-inflammation - Ngoc Nha Thao, Nguyen; Thi Trang Dai, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 1, 2024)
Published research showed that mango seeds have good anti-inflammatory and antibacterial properties. The purpose of this study is to develop a microemulsion formula containing mango seed extract for application in the treatment of inflammatory acne. Isopropyl myristate and coconut oil were selected as the fixed oil phase components. Phase diagrams for the microemulsion regions were constructed using PEG 40 hydrogenated castor oil as surfactant and PEG 400 as co-solvent. Microemulsions were prepared by titration and mixed with mango seed extract. Microemulsions and the physical and chemical stability of the microemulsion were evaluated for droplet size and PDi index using dynamic light scattering techniques. The microemulsion was gelled and evaluated for its anti-inflammatory effect by comparing it with an acne cream on the market. The selected microemulsion formula has a ratio of isopropyl myristate oil to coconut oil of 1:2, Smix/Co is PEG 40 hydrogenated castor oil to PEG 400 with a ratio of 3:1, and a high loading efficiency of 5% mango seed. The average particle size of the microemulsion reached 22.74 nm. The selected microemulsion showed good stability, with almost no change in particle size when stored at room temperature after 30 days. The microemulsion was gelled with 7% carbopol, and the permeability of polyphenols from the microemulsion gel within 6 hours was observed to be about 59.61%. The microemulsion gel inhibited the denaturation of bovine serum albumin, indicating that the microemulsion containing coconut oil and mango extract may help in treating inflammatory acne. Microemulsion gel containing mango seed kernel has been successfully studied, has anti-inflammatory activity equivalent to a modern control drug, and is promising as a natural preparation that can provide anti-inflammatory protection on acne skin. However, further clinical studies need to be conducted before use.